Microcatheter-assisted Trabeculotomy for Primary Congenital Glaucoma After Failed Glaucoma Surgeries. Issue 1 (January 2019) - Hu, Man; Wang, Huaizhou; Huang, Alex S.; Li, Li; Shi, Yan; Xu, Yongli; Wang, Ningli
Abstract : Purpose: To evaluate the effectiveness of microcatheter-assisted trabeculotomy (MAT) to treat primary congenital glaucoma after failed previous glaucoma surgeries. Materials and Methods: Retrospective, noncomparative, interventional case series conducted at Beijing Tongren Eye Center, China. Outcome measures were compared between 3 groups: successful and complete (≥330 degrees) MAT; successful and partial (<330 degrees) MAT; or cases converted to traditional trabeculotomy when the Schlemm's canal could not be catheterized >180 degrees. Success was defined as final intraocular pressure ⩽21 mm Hg, with (qualified success) or without (complete success) glaucoma medications. Results: In total, 74 eyes of 63 consecutive patients were included. MAT was performed in 50 eyes (67.6%). Postoperative intraocular pressure and number of glaucoma drops (17.7±8.6 mm Hg, 0.6±1.2 medications) was significantly less than the preoperative values (35.3±7.2 mm Hg, 2.7±0.8 medications; P <0.001). Cumulative probabilities of qualified and complete success were 84.0% and 80.0% at 3-year follow-up with no difference between complete and partial trabeculotomies. MAT was not successfully performed in 24 eyes (32.4%), requiring conversion to traditional trabeculotomy and associated with greater incidence of previous surgeries ( P <0.001), earlier age of disease onset ( P =0.024) and worse corneal transparency ( P =0.010). Cumulative probabilities of qualified and complete success were 37.0% and 29.2% at 3-year follow-up. Conclusions: Both complete and partial MAT achieved significant pressure reduction in cases of primary congenital glaucoma with previous failed glaucoma surgeries in intermediate term.